Utilization of Superheroes Social Skills to Reduce Disruptive and Aggressive Behavior. Issue 2 (2nd April 2016) - O'Handley, Roderick D.; Radley, Keith C.; Cavell, Hannah J.
Abstract : The current pilot study investigated the effectiveness of the Superheroes Social Skills program in decreasing disruptive and aggressive behavior of elementary-age students with high-incidence disabilities. Six students in a self-contained classroom, identified as displaying high rates of disruptive and aggressive behavior toward peers, were included in the study. Social skills training was presented over 10 lessons that targeted instructional control and turn taking skills. Results indicate immediate improvements in disruptive and aggressive behavior. Additionally, follow-up observations revealed maintenance of intervention effects. Sociometric data were collected, with all participants increasing in social network salience. Although use of an ABC design resulted in limited experimental control, preliminary results indicate that the Superheroes Social Skills program may be useful for addressing disruptive and aggressive behaviors.